A finite sample correction for the panel Durbin–Watson test. Issue 28 (15th June 2022) - Kim, Hyoungjong
ABSTRACT: This study shows that the panel Durbin–Watson d test is incapable of distinguishing temporal heteroskedasticity and serial correlation with short time series. The study proposes a new finite sample correction for solving this weakness of the panel Durbin–Watson test. Monte Carlo simulations demonstrate that the corrected statistic performs better in terms of size and power than the extant panel d tests. It leads to more accurate inferences in empirical studies.